Perceptions of smoking cessation and a novel psychosocial intervention for quitting among individuals with psychosis: A qualitative study. Issue 7 (22nd May 2021) - Moe, Aubrey M.; Keller‐Hamilton, Brittney; Lee, Angela; Breitborde, Nicholas J. K.; Ferketich, Amy K.
Abstract: Individuals diagnosed with psychosis have high rates of smoking‐related morbidity and early mortality. Only a small proportion of these smokers will attempt to quit, and many existing cessation interventions have limited effectiveness. To explore the unique and potentially unmet cessation needs of individuals with psychosis, we sought first‐person experiences with smoking cessation and reactions to a proposed intervention. Twenty‐four smokers with psychosis participated in focus group interviews. Multiple participants reported previous quit attempts using pharmacotherapy or behavioral methods, but few indicated they had previously tried cessation counseling. Though some individuals reported modest success with cessation, most participants tended to express negative perceptions of many available cessation approaches. When informed about the development of a novel smoking cessation intervention, participants had mixed but generally positive perceptions. Smokers diagnosed with psychosis are interested in sustained, individualized delivery of cessation services as part of their broader mental health care.